Carbene-catalyzed enantioselective aldol reaction : post-aldol stereochemistry control and formation of quaternary stereogenic centers - Yang, Xing (2021)
The dominated approaches for asymmetric aldol reactions have primarily focused on the aldol carbon-carbon bond-forming events. Here we postulate and develop a new catalytic strategy that seeks to modulate the reaction thermodynamics and control the product enantioselectivities via post-aldol processes. Specifically, an NHC catalyst is used to activate a masked enolate substrate (vinyl carbonate) to promote the aldol reaction in a non-enantioselective manner. This reversible aldol event is subsequently followed by an enantioselective acylative kinetic resolution that is mediated by the same (chiral) NHC catalyst without introducing any additional substance. This post-aldol process takes care of the enantioselectivity issues and drives the otherwise reversible aldol reaction toward a complete conversion. The acylated aldol products bearing quaternary/tetrasubstituted carbon stereogenic centers are formed in good yields and high optical purities.